2010
DOI: 10.1161/atvbaha.110.203901
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Stabilizes Microvascular Endothelial Barrier Function via Phosphatidylinositol 3-Kinase/Akt-Mediated Rac1 Activation

Abstract: Objective-Insulin is a key regulator of metabolism, but it also confers protective effects on the cardiovascular system.Here, we analyze the mechanism by which insulin stabilizes endothelial barrier function. Methods and Results-Insulin reduced basal and antagonized tumor necrosis factor-␣-induced macromolecule permeability of rat coronary microvascular endothelial monolayers. It also abolished reperfusion-induced vascular leakage in isolated-perfused rat hearts. Insulin induced dephosphorylation of the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…45,46 According to the results of this study, platelet Rac1 is activated by PDK1 in response to the GPVI agonist CRP. These findings are in line with broad evidence from other cells and diseases showing that Rac1 is activated by PI3K/Akt-dependent signaling 47 and with a recent study identifying Rac1 as a downstream target of PDK1. 29 As suggested by comparison with platelets isolated from rac1 −/− mice,…”
Section: +supporting
confidence: 90%
“…45,46 According to the results of this study, platelet Rac1 is activated by PDK1 in response to the GPVI agonist CRP. These findings are in line with broad evidence from other cells and diseases showing that Rac1 is activated by PI3K/Akt-dependent signaling 47 and with a recent study identifying Rac1 as a downstream target of PDK1. 29 As suggested by comparison with platelets isolated from rac1 −/− mice,…”
Section: +supporting
confidence: 90%
“…Subsequent to the publishing of our work, others showed that the small GTPase Rac1 is important in controlling microvessel permeability [15], and confirmed that insulin stabilizes microvascular endothelial barrier function via phosphatidylinositol 3-kinase/Akt-mediated Rac1 [16]. Based on these findings, we tested the possibility that insulin inhibits increased microvascular permeability induced by inflammatory agents.…”
Section: Discussionsupporting
confidence: 62%
“…Our previous work showed that insulin stimulates angiogenesis through the PI3K-Akt-Rac1 signal pathway and that the microvessels have many more αSMA-producing cells associated with them than controls, suggesting that it stimulates vessel stability potentially increasing barrier function [14]. These results have been subsequently confirmed by others [15,16]. Therefore, we hypothesize that the ability of insulin to increase barrier function (i.e., decrease vessel permeability) results in antagonizing the function of molecules such as thrombin, which stimulate the breakdown of barrier function (i.e., increase vessel permeability).…”
Section: Introductionmentioning
confidence: 57%
“…Other aspects of insulin signaling likely contribute. For example, insulin was also found to enhance endothelial cell-cell barrier function at adherens junctions, and this could be seen as anti-inflammatory (672).…”
Section: A Receptor Tyrosine Kinasesmentioning
confidence: 99%